PARTISIPASI POLITIK PADA PENDUDUK SIRKULER DALAM PEMILIHAN GUBERNUR JAWA TENGAH TAHUN 2013 (STUDI DI KELURAHAN BULUKERTO KECAMATAN BULUKERTO KABUPATEN WONOGIRI) - Lusiani, Santi; ., Winarno; Muchtarom, Moh. (Prodi PPKn FKIP UNS, 2017)
This study used a qualitative approach with descriptive form of research. Data sources are used consisted of: informants, places , events and documents. Sampling technique that be used is purposive sampling. Techniques of data collection through observation, interviews, and documentation. Validity of the data by using triangulation of data and triangulation methods. While, the analysis is using interactive techniques of analysis, namely data collection, data reduction, data presentation, and conclusion.The results showed that: (1) Political participations of the circular citizen in Bulukerto village in Central Java?s guvernor election in 2013 only on the vote, discussion and socializing. The use of suffrage only 30.09% of the total circular population in the Bulukerto village. In the socialization activity only 1 of 18 informants and discussion only 4 of 18 informants. (2) Factors that affect the participation of circular residents in Bulukerto villages influenced by factors within the individual that is because a) the mindset of people who do not believe in government, b) figure candidates for governor and lieutenant governor are less popular among the people. While the external factors because a) a job factors, the majority of circular citizen chose not to leave the job rather than voting, b) other factors are the polling places is so far from the city circuler population mobility, c) in administrative, circular populations are not enrolled in Daftar Pemilihan Tetap (DPT), and also they did not get an invitation. Kata kunci : partisipasi politik, pemilihan gubernur